Identifikasi Cemaran Bakteri Escherichia Coli Pada Ikan Layang (Decapterus Russelli) Segar Di Berbagai Pasar Kota Palu - Safriyanto S Maruka; Gatot Siswohutomo; Rostiati Dg Rahmatu (Mitra Sains, 2017)
Production of fresh fish that is high enough requires good handling technology for fish susceptible to the decay process. Handling fresh fish is still unfavorable in terms of security, including the process of handling the fish after rigor mortis, especially when viewed from the aspect of sanitation and hygiene. Consequently fish up into the hands of the seller before the consumers, had been contaminated by chemical contaminants, physical, and microbiological. The study aims to identify Escherichia coli bacterial contamination on fish float (Decapterus russelli) in various markets Palu. Research using descriptive analysis with Total Plate Count testing and identification of the bacterium Escherichia coli. The result of the identification of Escherichia coli bacteria in three markets in the city of Palu showed that all positive fish are Escherichia coli, where the Presidential Market with the number 210 APM / g, Market Masomba the amount of 3.0 APM / g, and 27 APM / g and Markets parents of 35 APM / g. Based on the results of testing of Escherichia coli showed that fish float in three different markets in the city of Palu have exceeded the maximum contaminant ISO 7388-2009 bacterium Escherichia coli on fresh fish that is <3 / g.